Evolution of accounting rules for Small and Medium-Sized Business Entities - S. N. Grichkina; I. V. Safonova (Учёт. Анализ. Аудит)
The object of this study is problematic issues regarding updating accounting rules in small and medium-sized businesses (IFRS for SMEs) in digitalization. The authors give a critical analysis of significant simplifications in the accounting system and accounting (financial) reporting in the Federal Accounting Standards (FSBU) and other legal acts regulating the accounting and reporting of small and medium-sized businesses. Based on the results of the work, the authors concluded on the advisability of applying certain simplified requirements for the formation and disclosure of financial information by small businesses, considering a thorough check of each of them for negative consequences in the usefulness’s context of this information; the lack of demand for “outdated” recommendations was revealed and the rationality of their cancellation was substantiated. The research showed that in the use’s context of digital technologies, additional IT opportunities are being formed to ensure the information transparency of SME activities and improve the quality of reporting information in sustainable development. The opinion about necessity to develop a separate Federal Accounting Standard for small and medium-sized businesses is substantiated. In the study’s course, the authors applied the methods of analysis, synthesis, comparison, systematic and logical approaches, accepted accounting principles that ensure the usefulness of information for interested users. The obtained results are aimed at the development of accounting practices in the new economic conditions.